(untitled) (Asian Journal of Medical and Biological Research, 2022)
Stimulating hormone for artificial fish breeding in hatchery industry is very crucial for hatching operation, healthy fry and fingerling production, while overall fish production of a country. The present study was conducted to assess the effectiveness of using local and overseas Carp Pituitary Gland (CPG) in the induced breeding of Cirrhinus mrigala at Jashore district from April to May 2022. The first dose of hormone, both for male and female brood fishes were injected with local and overseas CPG at 0.5mg/kg body weight. After six hours of the first dose, only female brood fishes were injected with the second dose of PG at 5 mg/kg body weight. After 6 hours of second dose CPG injection of local and overseas PGs, brood fishes started spawning. The ovulation rates for both local and overseas PGs were estimated 100%. The fertilization rates were 93.5 % and 92.6 % for local and overseas PGs; while the hatching rates were 91.2% and 89.5%, respectively. However, local CPG is highly recommended to hatchery owners considering the rate of fertilization, hatching rate and availability. Asian J. Med. Biol. Res. 2022, 8 (3), 146-153